Evaluation of allogenic hepato-tissue engineered in porous TiNi-based scaffolds for liver regeneration in a CCl4-induced cirrhosis rat model. (15th January 2019) - Kokorev, Оleg; Hodorenko, Valentina; Chekalkin, Timofey; Gunther, Victor; Kang, Seung-Baik; Chang, Moon-Jong; Kang, Ji-Hoon
Abstract: The study aimed to explore the in vivo applicability of intracorporeal constructions with hepatocytes cultured in the porous TiNi-based scaffold (PTNS). We also sought to determine whether application of hepatocytes cultured in the PTNS was superior to sham operation or simple hepatocyte injection in terms of restoration of liver functions and survival time in a CCl4 -induced hepatitis rat model. Using 12 animals, image analysis of SEM data of in vivo hepatocyte evolution in the PTNS was carried out. In addition, 200 animals were assigned to explore the experimental groups as follows: (1) Group I, control group; (2) Group II, animals with toxic hepatitis; (3) Group III, animals with toxic hepatitis followed by implantation of cell-free PTNS (sham-surgery); 4) Group IV, animals with toxic hepatitis followed by infusion of hepatocytes only (15 × 10 6 cells ml −1 ); 5) Group V, animals with toxic hepatitis followed by implantation of hepatocytes cultured in the PTNS. In the SEM analysis, hepatocytes demonstrated good adhesion and proliferation in the pore space of the PTNS. Moreover, mature tissue comprising both colloidal and fibrous components filled the pore body by 95% in 28 days. Concerning restoration of liver function, Group V showed a significant reduction of serum alanine aminotransferase level compared to Group II. Group IV also showed a significant decrease in ALT level at 15 days. However, the level of ALT increased at 30 days, and the level was similar with results of the group II. This situation probably was caused by a short-term effect of hepatocyte injection only. The change patterns of serum protein, lactate, albumin, fibrinogen, and total bilirubin levels were similar to the results of ALT. The survival time of animals was significantly longer in Group V. These findings showed possible abilities of the PTNS as a scaffold to support the hepatocellular metabolism. Overall, this study sheds a different light on how the implantable «auxiliary liver» by engrafting the cultured PTNS substitutes the missing hepatic function without the need to replace the whole liver.